Direct Oral Anticoagulants Versus Warfarin in the Treatment of Cerebral Venous Thrombosis (ACTION-CVT): A Multicenter International Study. Issue 3 (March 2022) - Yaghi, Shadi; Shu, Liqi; Bakradze, Ekaterina; Salehi Omran, Setareh; Giles, James A.; Amar, Jordan Y.; Henninger, Nils; Elnazeir, Marwa; Liberman, Ava L.; Moncrieffe, Khadean; Lu, Jenny; Sharma, Richa; et al.
Abstract : Background: A small randomized controlled trial suggested that dabigatran may be as effective as warfarin in the treatment of cerebral venous thrombosis (CVT). We aimed to compare direct oral anticoagulants (DOACs) to warfarin in a real-world CVT cohort. Methods: This multicenter international retrospective study (United States, Europe, New Zealand) included consecutive patients with CVT treated with oral anticoagulation from January 2015 to December 2020. We abstracted demographics and CVT risk factors, hypercoagulable labs, baseline imaging data, and clinical and radiological outcomes from medical records. We used adjusted inverse probability of treatment weighted Cox-regression models to compare recurrent cerebral or systemic venous thrombosis, death, and major hemorrhage in patients treated with warfarin versus DOACs. We performed adjusted inverse probability of treatment weighted logistic regression to compare recanalization rates on follow-up imaging across the 2 treatments groups. Results: Among 1025 CVT patients across 27 centers, 845 patients met our inclusion criteria. Mean age was 44.8 years, 64.7% were women; 33.0% received DOAC only, 51.8% received warfarin only, and 15.1% received both treatments at different times. During a median follow-up of 345 (interquartile range, 140–720) days, there were 5.68 recurrent venous thrombosis, 3.77 major hemorrhages, and 1.84 deaths per 100 patient-years. Among 525 patients who met recanalization analysis inclusion criteria, 36.6% had complete, 48.2% had partial, and 15.2% had no recanalization. When compared with warfarin, DOAC treatment was associated with similar risk of recurrent venous thrombosis (aHR, 0.94 [95% CI, 0.51–1.73]; P =0.84), death (aHR, 0.78 [95% CI, 0.22–2.76]; P =0.70), and rate of partial/complete recanalization (aOR, 0.92 [95% CI, 0.48–1.73]; P =0.79), but a lower risk of major hemorrhage (aHR, 0.35 [95% CI, 0.15–0.82]; P =0.02). Conclusions: In patients with CVT, treatment with DOACs was associated with similar clinical and radiographic outcomes and favorable safety profile when compared with warfarin treatment. Our findings need confirmation by large prospective or randomized studies. Abstract : Supplemental Digital Content is available in the text.